Conscience and Conformity: Societal Roles and Individual Actions in Katherine Mansfield’s “The Garden Party” and George Orwell’s “Shooting an Elephant” - Imam, Rabby (International Journal of Language and Literary Studies, 2025)
Through a comparative analysis of Katherine Mansfield’s “The Garden Party” (1922) and George Orwell’s “Shooting an Elephant” (1936), this paper argues that both authors uncover how social conformity—rooted in class and empire—systematically suppresses moral autonomy and distorts human conscience. While Mansfield situates her critique within postwar English social hierarchies and Orwell within the structures of British colonial power, both reveal how societal expectations dictate behavior and distort moral agency. Through qualitative, interpretive, and comparative analysis grounded in modernist ethics and postcolonial criticism, the study argues that both authors expose the performative mechanisms by which social order sustains itself—through the silencing of conscience and the valorization of conformity. By juxtaposing Mansfield’s domestic modernism with Orwell’s colonial narrative, this research contributes to the broader literary discourse on morality and power by identifying a shared ethical trajectory between two seemingly disparate traditions. It reveals that class and empire operate as parallel systems of coercion that compel individuals toward moral compromise. The paper thus advances the understanding of early twentieth-century literature as a site where aesthetic form becomes an instrument of ethical inquiry, bridging modernist and postcolonial studies through the theme of conscience under constraint.